Simultaneous assessment of lung morphology and respiratory motion in retrospectively gated in-vivo microCT of free breathing anesthetized mice - Dullin, Christian; Svetlove, Angelika; Zschüntzsch, Jana; Alves, Frauke (Scientific reports, 2022)
Retrospective gating (RG) is a well established technique in preclinical computed tomography (CT) to assess 3D morphology of the lung. In RG additional angular projections are recorded typically by performing multiple rotations. Consequently, the projections are sorted according to the expansion state of the chest and those sets are then reconstructed separately. Thus, the breathing motion artefacts are suppressed at a cost of strongly elevated X-ray dose levels. Here we propose to use the entire raw data to assess respiratory motion in addition to retrospectively gated 3D reconstruction that visualize anatomical structures of the lung. Using this RG based X-ray respiratory motion measurement approach, which will be referred to as RG based X-ray lung function measurement (rgXLF) on the example of the mdx mouse model of Duchenne muscle dystrophy (mdx) we accurately obtained both the 3D anatomical morphology of the lung and the thoracic bones as well as functional temporal parameters of the lung. Thus, rgXLF will remove the necessity for separate acquisition procedures by being able to reproduce comparable results to the previously established planar X-ray based lung function measurement approach in a single low dose CT scan.